Meningkatkan Kemampuan Membaca Pemahaman Dengan Menggunakan Metode Speed Reading Pada Siswa Kelas V SD Negeri 1 Poka: Indonesia - Ningsih; Ririhena, Ribka L; Sahetapy, Sarah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The purpose of this study was to determine how to improve reading comprehension skills using the Speed Reading method in grade V students of SD Negeri 1 Poka in the 2024/2025 academic year. This study was a Classroom Action Research (CAR). The subjects were 19 grade V students. The results showed that using the Speed Reading learning method can improve students' reading comprehension skills. The study revealed that the average student learning outcome score in the pre-action phase increased from 53.05% to 63.68% in Cycle I, and in Cycle II, increased to 83.50%. Based on the research results, it can be concluded that in cycle II, students have classically completed their learning, as 83.50% of students obtained a score of 70 or higher, exceeding the desired completion percentage of 70%. This proves that the use of the Speed Reading method can improve the reading comprehension skills of fifth-grade students at SD Negeri 1 Poka in the 2024/2025 academic year.